2007
DOI: 10.1158/1535-7163.mct-06-0592
|View full text |Cite
|
Sign up to set email alerts
|

Development of two novel benzoylphenylurea sulfur analogues and evidence that the microtubule-associated protein tau is predictive of their activity in pancreatic cancer

Abstract: In this work, we evaluated two lead compounds, referred to as SG410 and SG430, obtained from a screen of sulfur benzoylphenylurea analogues, against in vitro and in vivo models of pancreas cancer. Both drugs showed a similar mechanism of action profile, with SG410 being more potent as an inhibitor of tubulin assembly. We determined the best in vivo administration schedule and tested SG410 and SG430 in nine cases of a novel platform of direct pancreas cancer xenografts. Both compounds had antiproliferative acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The results of our in vitro study indicated that expression of MAPT protein isoforms less than 70 KDa had the most influence on sensitivity to taxanes. A discrepancy between MAPT mRNA expression and protein expression has been found previously [37], and thus analysis of MAPT mRNA expression may not be appropriate for examining the utility of MAPT as a predictor of taxane sensitivity. Furthermore, the status of the expression of different MAPT protein isoforms is important in determining sensitivity to taxanes, but immunohistochemistry cannot be used to evaluate each isoform.…”
Section: Discussionmentioning
confidence: 95%
“…The results of our in vitro study indicated that expression of MAPT protein isoforms less than 70 KDa had the most influence on sensitivity to taxanes. A discrepancy between MAPT mRNA expression and protein expression has been found previously [37], and thus analysis of MAPT mRNA expression may not be appropriate for examining the utility of MAPT as a predictor of taxane sensitivity. Furthermore, the status of the expression of different MAPT protein isoforms is important in determining sensitivity to taxanes, but immunohistochemistry cannot be used to evaluate each isoform.…”
Section: Discussionmentioning
confidence: 95%
“…Tau expression has been reported in muscle, liver, kidney, and other tissues 40; 41 . It has also been found in human breast, prostate, gastric, and pancreatic cancer cell lines and tissues 42; 43; 44; 45; 46 , as well as in the muscle cells of individuals with inclusion body myositis 47 . The function of tau in non-neuronal cells remains to be elucidated and functions outside of the cytoskeleton may have significance for neurodegenerative disease.…”
Section: Tau Gene and Isoformsmentioning
confidence: 94%
“…Tau expression has also been noticed in different non-neuronal cells like those of the liver, kidney, muscle and so on [126,127] Tau protein has also been expressed in human breast, prostate, gastric and pancreatic cancer cell lines and tissues [12][13][14][15][16]. Tau is also found in patients with twisted tubulofilaments of inclusion-body myositis [19].…”
Section: Tau In Cancermentioning
confidence: 99%
“…In addition to neurons, tau expression has been noticed in human breast, prostate, gastric, colorectal and pancreatic cancer cell lines and tissues [12][13][14][15][16][17][18]. Tau is also found in patients with twisted tubulofilamentous of inclusion-body myositis [19].…”
Section: Introductionmentioning
confidence: 99%